A bridge to cross. Legal education, the civil lawyers and the common law: an Italian perspective - Graziadei, Michele (2018)
Why should lawyers based in a civil law country study the common law? Is this study important for the formation of jurists who will mostly practice the law in a civil law jurisdiction? These are important questions that have no obvious, ready-made answers. In the following pages, I will offer a personal point of view on these matters drawing from my experience as a comparative law professor based in Italy. As such, I have dedicated enough time to studying and teaching the common law to generations of law students, both as a stand-alone subject, and as part of comparative law courses that make up part of the core law school curriculum in Italy.